Physical modeling of the formation of the clathrate hydrates of methane - Drobyshev, A.; Aldiyarov, A.; Katpaeva, K.; Korshikov, E.; Kurnosov, V.; Shinbayeva, A.; Sokolov, D.; Timchenko, A. (Хабаршы. Физика сериясы, 2015)
Nowadays natural gas hydrates attract special attention as a possible source of fossil fuel. According to various estimates, the reserves of hydrocarbons in hydrates exceed considerably explored reserves of natural gas. Due to the clathrate structure the unit volume of the gas hydrate can contain up to 160-180 volumes of pure gas.